Quantitative and Fiber-Selective Evaluation for Central Poststroke Pain - Jian-Min Chen; Qing-Fa Chen; Zhi-Yong Wang; Guo-Xin Ni (Neural Plasticity)
The electrophysiological recording can be used to quantify the clinical features of central poststroke pain (CPSP) caused by different lesion locations. We aimed to explore the relationship between clinical features and lesion location in patients with CPSP using the current perception threshold (CPT) approach. Here, patients underwent the standardized CPT measure at five detection sites on both the contralesional and ipsilesional sides, using a constant alternating-current sinusoid waveform stimulus at three frequencies: 2000 Hz, 250 Hz, and 5 Hz. 57 CPSP patients were recruited in this cross-sectional study, including 13 patients with thalamic lesions and 44 patients with internal capsule lesions. Patients with a thalamic lesion had more frequent abnormal Aδ and C fibers than those with an internal capsule lesion (69.2% versus 36.4%, p value = 0.038; 53.8% versus 63.6%, p value = 0.038). The patients with internal capsule lesions had more frequent abnormal Aβ fibers than those with thalamic lesions (53.8% versus 63.6%, p value < 0.001). The sensory dysfunction in the patients with thalamic lesions was more likely to occur in the upper limbs (i.e., the shoulder (p value = 0.027) and the finger (p value = 0.040)). The lower limbs (i.e., the knee (p value = 0.040) and the toe (p value = 0.005)) were more likely to experience sensory dysfunction in the patients with internal capsule lesions. Hyperesthesia was more likely to occur in the thalamic patients, and hypoesthesia was more likely to occur in the patients with internal capsule lesions (p value < 0.001). In patients with thalamic lesions, Visual Analogue Scale (VAS) had a positive correlation with 5 Hz CPT on the shoulder (r=0.010, p value = 0.005), 250 Hz CPT on the finger (r=0.690, p value = 0.009) from the contralesional side, and 2000 Hz CPT on the knee (r=0.690, p value = 0.009). In patients with internal capsule lesions, VAS had a positive correlation with 2000 Hz CPT on the knee (r=0.312, p value = 0.039) and foot (r=0.538, p value < 0.001). In conclusion, the abnormal fiber types, sensory dysfunction territory, and clinical signs of CPSP in thalamic stroke differ from those in internal capsule stroke. Implementation of the portable and convenient CPT protocol may help clarify the locations of different stroke lesions in various clinical settings.